Corporate Governance and MENA Banks Performance - Luis Otero González; Pablo Durán-Santomil; Rafat Alaraj (Revista de Economía Mundial, 2021)
We analyze the effect of corporate governance on banks’ performance in the MENA countries using an index comprised of seven widely used governance measures, as a measure of firm-level corporate governance. In addition, we have also considered country governance as an important determinant of performance. The data at the firm level has been obtained from the Bankscope Database and we also hand-collect the corporate governance data from the annual reports over the period 2005-2012, covering the period of the financial crisis. At the country level we obtain the data from different sources. Our paper shows that corporate governance is relevant explaining performance in a way consistent with the segmentation of the corporate governance at both country level and bank level. It highlights the need for internal governance mechanisms but also the importance of country governance in emerging markets. The best governance at the country level has a positive effect under favorable conditions but not in crisis situations.